A case of takotsubo cardiomyopathy developing ventricular fibrillation after a pacemaker implantation. Issue 4 (April 2020) - Wakatsuki, Daisuke; Asano, Taku; Mase, Hiroshi; Kurata, Masaaki; Suzuki, Hiroshi
Abstract: Pacemaker implantations are minimally invasive procedures commonly used for patients with bradycardic arrhythmias. Takotsubo cardiomyopathy, which is usually induced by life-threatening stress hardly ever occurs after this minimally invasive procedure. Here, we experienced a patient who developed takotsubo cardiomyopathy leading to ventricular fibrillation the day after a pacemaker implantation. At that time, a cardiac echocardiogram and left ventriculogram revealed hypercontraction of the base of the heart and a decreased contraction of the apex. A coronary angiogram revealed no significant coronary stenosis. Ten days later, the electrocardiogram findings normalized, and an echocardiogram revealed that the left ventricular function had fully recovered. Therefore, we diagnosed this patient with takotsubo cardiomyopathy. In general, pacemaker implantations are routine procedures and fatal complications are low. We report a case that developed potentially fatal complications after a pacemaker implantation. <Learning objective: This patient developed in-hospital cardiac arrest due to ventricular fibrillation from takotsubo cardiomyopathy after a pacemaker implantation, which is of special interest because complications leading to in-hospital cardiac arrest just after a pacemaker implantation are rare. We consider this case report as an educational case that caused potentially fatal complications even after pacemaker implantation.>